2021
DOI: 10.1080/22221751.2020.1868950
|View full text |Cite
|
Sign up to set email alerts
|

Increasing prevalence of hypervirulent ST5 methicillin susceptible Staphylococcus aureus subtype poses a serious clinical threat

Abstract: Staphylococcus aureus ( S. aureus ) is a clinical pathogen of great significance causing metastatic or complicated infections. ST5 clonotype isolates have dominated S. aureus infections for more than 10 years in Shanghai, China, and the proportion of methicillin-susceptible S. aureus (MSSA) has remarkably increased in the past decades. By whole-genome sequencing (WGS) 121 ST5 clonotype S. aureus isolates usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 57 publications
(70 reference statements)
4
19
0
Order By: Relevance
“…Enhanced virulence activity has recently been suggested as a contributor to the increasing prevalence of another CA-MRSA ST5 in China, including in MSSA [83]. Our findings lend further support to this hypothesis, with the carriage of chp as a potentially major contributor to the ongoing prevalence of ST59 strains in China, likely at the expense of ST239.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Enhanced virulence activity has recently been suggested as a contributor to the increasing prevalence of another CA-MRSA ST5 in China, including in MSSA [83]. Our findings lend further support to this hypothesis, with the carriage of chp as a potentially major contributor to the ongoing prevalence of ST59 strains in China, likely at the expense of ST239.…”
Section: Discussionsupporting
confidence: 84%
“…Virulence as a measurable trait ultimately requires evaluation using in vivo models though cytolytic activity, which can be readily measured using lysis of erythrocyte assays, offers a good proxy given hemolysins are wellestablished virulence factors [81]. Higher cytolytic activity as a virulence mechanism in our ST59 isolates is consistent with pronounced measurements of virulence in ST59 lineages [82] and the role of the innate immune evasion cluster in mouse infection models [83]. In our dataset, we identified, through a knock-out experiment, that the mechanism enhancing the virulence of ST59 in China can be well explained by the carriage of a single gene, encoding CHIPS (chp).…”
Section: Discussionsupporting
confidence: 62%
“…A recent study by Jian et al ( 25 ) reconstructed the phylogeny of ST5 strains isolated from an affiliated tertiary hospital in China between 2008 and 2018. Those authors reported that ST5 MSSA isolates evolved independently in a manner distinct from ST5 MRSA isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Hemolysis assay. The hemolysis assay was conducted as follows [ 25 ]. The bacteria were cultured for 8 h in 3 ml TSB with shaking (200 rpm) using 15 ml tubes.…”
Section: Methodsmentioning
confidence: 99%